2024
DOI: 10.1038/s41586-023-06990-w
|View full text |Cite
|
Sign up to set email alerts
|

Bile salt hydrolase catalyses formation of amine-conjugated bile acids

Bipin Rimal,
Stephanie L. Collins,
Ceylan E. Tanes
et al.

Abstract: Bacteria in the gastrointestinal tract produce amino acid bile acid amidates that can affect host-mediated metabolic processes1–6; however, the bacterial gene(s) responsible for their production remain unknown. Herein, we report that bile salt hydrolase (BSH) possesses dual functions in bile acid metabolism. Specifically, we identified a previously unknown role for BSH as an amine N-acyltransferase that conjugates amines to bile acids, thus forming bacterial bile acid amidates (BBAAs). To characterize this ami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Previously unrecognized amine N -acyl transferase activity of bsh, a ubiquitous bacterial enzyme that catalyzes deconjugation of host bile salts, appears to be involved in the formation of MBSCs. 33 Additional biosynthetic pathways likely exist, as suggested by MBSC production by bacteria seemingly devoid of bsh . 33 Notwithstanding the advances in basic aspects of MBSCs, insight into their biological function(s) is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously unrecognized amine N -acyl transferase activity of bsh, a ubiquitous bacterial enzyme that catalyzes deconjugation of host bile salts, appears to be involved in the formation of MBSCs. 33 Additional biosynthetic pathways likely exist, as suggested by MBSC production by bacteria seemingly devoid of bsh . 33 Notwithstanding the advances in basic aspects of MBSCs, insight into their biological function(s) is limited.…”
Section: Discussionmentioning
confidence: 99%
“… 33 Additional biosynthetic pathways likely exist, as suggested by MBSC production by bacteria seemingly devoid of bsh . 33 Notwithstanding the advances in basic aspects of MBSCs, insight into their biological function(s) is limited. To appreciate a role in host bile salt signaling, we studied the interaction of MBSCs with the key bile salt receptors TGR5 and FXR.…”
Section: Discussionmentioning
confidence: 99%
“…185 Recently, Patterson's and Quinn's groups reported that bile salt hydrolase (BSH) not only plays a role in bile acid metabolism but also acts as an amine N -acyltransferase, forming bacterial bile acid amidates (BBAAs). 186,187 BSH belongs to the N-terminal nucleophile superfamily of enzymes and catalyzes the hydrolysis of glycocholic acid ( 142 ) and taurocholic acid ( 143 ) to generate BBAAs (Fig. 25).…”
Section: Amination and Amidationmentioning
confidence: 99%
“… 104 These MCBAs can activate PXR receptor and the aryl hydrocarbon receptor. 105 The intrinsic acyltransferase activity of BSH/T greatly diversifies BA chemistry. The physiological effects of amino acid-conjugated BAs, other than those conjugated to glycine or taurine, are not yet fully understood.…”
Section: Mechanisms Of Bile Acid Biotransformation By Gut Microbiotamentioning
confidence: 99%